Fortified Coiled Coils: Enhancing Mechanical Stability with Lactam or Metal Staples. Issue 1 (29th October 2020) - López‐García, Patricia; de Araujo, Aline D.; Bergues‐Pupo, Ana E.; Tunn, Isabell; Fairlie, David P.; Blank, Kerstin G.
Abstract: Coiled coils (CCs) are powerful supramolecular building blocks for biomimetic materials, increasingly used for their mechanical properties. Here, we introduce helix‐inducing macrocyclic constraints, so‐called staples, to tune thermodynamic and mechanical stability of CCs. We show that thermodynamic stabilization of CCs against helix uncoiling primarily depends on the number of staples, whereas staple positioning controls CC mechanical stability. Inserting a covalent lactam staple at one key force application point significantly increases the barrier to force‐induced CC dissociation and reduces structural deformity. A reversible His‐Ni 2+ ‐His metal staple also increases CC stability, but ruptures upon mechanical loading to allow helix uncoiling. Staple type, position and number are key design parameters in using helical macrocyclic templates for fine‐tuning CC properties in emerging biomaterials. Abstract : Staple it! A terminal helical turn in heterodimeric coiled coils was stapled with a covalent lactam or a reversible metal‐coordination bond. The staples provide resistance to helix uncoiling and increase coiled coil stability to thermal denaturation and external mechanical forces.